FOREIGN POLICY OF THE NEW UZBEKISTAN AND ITS FEATURES - Yuldasheva Govkherjan (Scholar Express Journals, 2023)
This article is devoted to of the new foreign policy of the Republic of Uzbekistan, it examines the main goals of the foreign policy activities of the Republic of Uzbekistan, analyzes the priority areas of foreign policy identified in the New Development Strategy of Uzbekistan for 2022-2026 and identifies the features of the foreign policy of the new Uzbekistan, as well as theoretical conclusions have been drawn on this issue
Keywords: Foreign policy; main goals of foreign policy; the Republic of Uzbekistan